A Natural Carbon Encapsulated in Gellan-Based Hydrogel Particles Designed for Environmental Challenges - Camelia-Elena Tincu (Iurciuc); Mihaela Hamcerencu; Marius Sebastian Secula; Corneliu Sergiu Stan; Cristina Albu; Marcel Popa; Irina Volf (Gels)
This article reports the obtention of a new gellan-based hydrogel linked with Fe3+ and loaded with a natural micro/nanostructured carbon designed as a contaminant’s removal from wastewater. Hydrogels are known for their water-retaining properties, high binding capacity, and eco-friendly features. The new material is expected to behave as one cost-effective and efficient sorbent, including natural carbon structures with various functional groups. The encapsulation efficiency ranges between 89% and 95%. The obtained hydrogel particles were characterized using FT-IR spectroscopy and scanning electron microscopy techniques. The hydrogel particles’ water stability was evaluated by measuring the transmittance for 10 days, and the capacity to retain water was assessed by determining the swelling degree (Q%). The results showed that hydrogel particles are stable (the transmittance value is higher than 97.8% after 10 days), and their properties are influenced by the cross-linking degree, the amount of the carbon particles encapsulated, and the concentration of gellan. For example, the Q% values and encapsulation efficiency increased when the cross-linking degree, the carbon microstructure quantity, and the gellan concentration decreased. The new hybrid material can retain Pb(II) ions and diclofenac molecules, and could be used in different adsorption–desorption cycles.